[PP.22.06] PLASMA D-DIMER LEVELS ARE RELATED TO INTRARENAL VASCULAR RESISTANCE IN NON-DIABETIC ESSENTIAL HYPERTENSIVE PATIENTS. (September 2016) - Catena, C.; Colussi, G.L.; Novello, M.; Martinis, F.; Nait, F.; Sechi, L.A.
Abstract : Objective: Hypertensive nephroangiosclerosis is characterized by progressive narrowing of preglomerular arterioles that leads to increased intrarenal vascular resistance. This can be estimated by duplex ultrasound evaluation and measurement of the intrarenal resistance index (IR). In addition to high blood pressure, other factors can contribute to development and progression of nephroangiosclerosis. The aim of this study was to investigate the possible relationships between some emergent cardiovascular risk factors, such as a prothrombotic state, and presence and severity of nephroangiosclerosis, as evaluated by measurement of IR, in hypertension. Design and method: In 115 non-diabetic, essential hypertensive patients (age 46 ± 13 years; 63 males, 57 never treated with anti-hypertensive drugs, 58 studied after drug wash-out of at least 2 weeks) we measured anthropometric variables, fasting plasma glucose and insulin, HOMA-index, 24-h creatinine clearance (CrCl) and urinary protein excretion, plasma levels of fibrinogen, D-dimer, prothrombin fragment 1 + 2, plasminogen activator inhibitor-1, tissue-plasminogen activator, lipoproteina (a), and homocysteine. Patients with CrCl < 30 ml/min/1.73 m 2 were excluded. In all patients, IR was calculated as the average of 4 to 6 separate measurements that were obtained in the interlobar arteries respectively in the upper, middle, and lower third of both kidneys and patients were subdivided according to tertiles of IR. Results: IR was greater in women than in men, and in patients previously treated with antihypertensive drugs. Patients in the highest tertile of IR were older and had greater body mass index, pulse pressure, D-dimer and fibrinogen levels, and lower CrCl than patients in lowest IR tertile. No differences in the other variables considered in the study were found across IR tertiles. At univariate analysis IR was significantly and directly related to age, systolic and pulse pressure, HOMA-index, urinary protein excretion, D-dimer, and inversely with CrCl. At multivariate analysis, IR was independently associated with pulse pressure, CrCl and D-dimer levels. Conclusions: In non-diabetic hypertensive patients subclinical damage of intrarenal vessels is related with an activation of the hemostatic system that could play a role in the early stages of hypertensive nephropathy.